2020
DOI: 10.1186/s12913-020-5011-3
|View full text |Cite
|
Sign up to set email alerts
|

External facilitators’ perceptions of internal facilitation skills during implementation of collaborative care for mental health teams: a qualitative analysis informed by the i-PARIHS framework

Abstract: Background: Facilitation is a key strategy that may contribute to successful implementation of healthcare innovations. In blended facilitation, external facilitators (EFs) guide and support internal facilitators (IFs) in directing implementation processes. Developers of the i-PARIHS framework propose that successful facilitation requires project management, team/ process, and influencing/negotiating skills. It is unclear what IF skills are most important in real-world settings, which could inform recruitment a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 19 publications
0
31
0
2
Order By: Relevance
“…Given these wide ranging activities, previous work has illustrated the importance of models of external facilitation that go beyond a lone facilitator [5,11,[16][17][18]. Researchers have described the roles and impacts of facilitator dyads, such as in blended external and internal facilitation designs [19][20][21][22][23][24], and mixed discipline facilitator designs [16][17][18]. These models involve sharing and coordinating different functions of facilitation, though manuscripts rarely detail how they work together.…”
Section: Introductionmentioning
confidence: 99%
“…Given these wide ranging activities, previous work has illustrated the importance of models of external facilitation that go beyond a lone facilitator [5,11,[16][17][18]. Researchers have described the roles and impacts of facilitator dyads, such as in blended external and internal facilitation designs [19][20][21][22][23][24], and mixed discipline facilitator designs [16][17][18]. These models involve sharing and coordinating different functions of facilitation, though manuscripts rarely detail how they work together.…”
Section: Introductionmentioning
confidence: 99%
“…For organizational barriers, Facilitation-based on the integrated-Promoting Action on Research Implementation in Health Services (i-PARIHS) [39] frameworkprovides schools with ongoing consultation from an expert in strategic thinking and EBP implementation to garner administrative support, solve logistical challenges, and build community buy-in. In several communitybased cluster-randomized trials, Facilitation has been shown to improve mental health EBP uptake [30,34,[40][41][42][43][44][45] and to be highly cost-effective [46,47].…”
Section: Introductionmentioning
confidence: 99%
“…This has been recognized by other researchers in the field, with some referring to it as blended facilitation where a teambased approach that leverages the complementary skills and expertise of external and internal facilitators is used. [22][23][24] Although there are commonalities, facilitation activities involved some level of local contextualization where there were unique or additional activities performed to accommodate the local needs and requirements of the health organization involved in each case, as well as methodological guidance or assistance with the development, implementation and analysis of findings and/or disseminating the findings. In this article, where cases of facilitation occurred as part of the JBI EITP, numerous contextual factors influenced the success of the implementation initiative.…”
Section: Discussionmentioning
confidence: 99%